Pengaruh Annealing Baja St 37 Terhadap Kekerasan Dan Kekuatan Tarik - ., Affandi; Nasution, Arya Rudi; Tanjung, Iqbal; Siregar, Ahmad Marabdi (Rekayasa Material, Manufaktur dan Energi, 2022)
Steel ST 37 which is equivalent to AISI (The American Iron Steel Institute) is one of the steels produced for the manufacture of various machine components. To improve the mechanical properties and material structure of ST 37 Steel, it is necessary to carry out the heat treatment (annealing) process. The objective of this study was to determine the annealing treatment of ST 37 steel on hardness and tensile strength to analyze the tensile test on ST 37 steel before and after annealing treatment and to analyze the hardness test of ST 37 steel before and after annealing treatment. The annealing process is carried out by preparing the test material and inserting the test material into the furnace and tightly closing the door of the heat treatment furnace. Set the temperature to be used in the test, which is 500C, and held for 60 minutes. Then turn off the furnace and leave the test specimens in the furnace for 72 hours to cool through the air cooling medium, after which tensile and hardness tests are carried out. The test results of the tensile test specimens with the ASTM E8/E8M standard and the hardness test specimens with the ASTM E18 standard are, the average value of the tensile test results before the annealing process is 50.65 kgf/mm and the average value of the tensile test results after the annealing process is 31.45 kgf/mm. While the average value of the hardness test before the annealing process was 75.22 HRA and the average value of the hardness test after the annealing process was 67.63 HRA. From these results, ST 37 steel before the annealing process has higher hardness and tensile strength. However, in subsequent tests, harder specimens can be used compared to ST 37 Steel specimens, and in the use of heat treatment furnaces, it is preferable to be in a state of heat safety.